Begräbnis der Revolutionsopfer: "Die Aufbahrung inmitten der unübersehbaren Volksmenge". Aus: Album XI
Begräbnis der Revolutionsopfer: "Die Aufbahrung inmitten der unübersehbaren Volksmenge". Aus: Album XI.